Effective Grassroots Social Action in Public Education - Willie, Charles V. (Journal of applied social science, 2009)
This article identifies public school education as a community affair which requires the talents of lawyers, social science scholars, and other kinds of people. Since public education is described as a community affair, diversity in student body and faculty is recommended as a way of gathering essential opinions on how education may benefit all individuals as well as the community. Grassroots strategies for achieving effective social action are discussed.